Experimental and numerical study of free-surface wave resonance in the gap between two elongated parallel boxes with square corners. (November 2020) - Wang, Hongchao; Zhao, Wenhua; Draper, S.; Wolgamot, H.A.; Taylor, P.H.
Abstract: Experiments with wave groups are carried out to investigate 3D wave resonance in the gap between two fixed parallel elongated boxes with square corners. The gap responses are re-created in a numerical wave tank using computational fluid dynamics (CFD) with reasonable accuracy. Based on the CFD results with high temporal and spatial resolution, the free-surface behaviour, internal flow velocity and vortex structures near the gap are interrogated in detail to gain insights into the behaviour. It is found that the damping which affects the oscillatory motion in the gap appears to be linear (or at least dominated by linear damping) except for the largest excitation, though substantial flow separation is present. A phase-based harmonic separation method is used to extract the harmonics of the wave field, which is found useful in understanding the dynamics of wave-structure interactions for gap resonance problems.